Leptura aurulenta (Coleoptera, Cerambycidae), a new record of a very rare species in Russia - Alexander B. Ruchin; Leonid V. Egorov (Nature Conservation Research: Заповедная наука, 2018)
The paper presents data on a new record of a very rare insect, Leptura aurulenta (Coleoptera, Cerambycidae), in the Mordovia State Nature Reserve (Russia). This is a third reliable registration of this species within Russia. It expands the range of this beetle to 600 km to the east. We have presented an original biotope description, data on distribution and biology of L. aurulenta.